Contribution of The Sociodrama Method in Stimulating Children’s Language Abilities - Putri Irma; Cirocki Andrzej (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2025)
The results of a preliminary study found that children's language skills were still low. This problem arose because the learning provided was teacher-centered and limited to LKA. This study aimed to determine the effect of the sociodrama method in stimulating the language skills of children aged 5-6 years. This study used a quantitative research type with an ex post facto design. The subjects in this study were 32 teachers and 32 parents of children at a Surabaya Kindergarten. Data collection in this study was through an online questionnaire distributed using Google Forms. Data analysis in this study used simple linear regression analysis. Based on the calculation results, this study found that the sociodrama method contributed positively to language skills, especially in the number of vocabulary used by children to express their feelings. This indicates that there is an effect of the sociodrama method on children's language skills, where every one percent of the sociodrama method applied increases the child's language ability score. This study has implications for parents and teachers in stimulating children's language skills, especially vocabulary related to expressing expressions and feelings in children.